1997
DOI: 10.1161/01.cir.96.2.599
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Sarcolemmal Na + ,K + -ATPase Activity Reduces the Infarct Size–Limiting Effect of Preconditioning in Rabbit Hearts

Abstract: Preconditioning preserves the ischemia-induced reduction in sarcolemmal Na+,K+-ATPase activity in the early phase of ischemia in rabbit hearts. Inhibition of Na+,K+-ATPase activity reduces the infarct size-limiting effect of preconditioning with a loss of increased Na+-Ca2+ exchange activity, implying that this preservation is responsible for the cardioprotective effect of preconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 25 publications
1
16
1
Order By: Relevance
“…Numerous studies have demonstrated a role for Na/KATPase in the heart's response to ischemia reperfusion (39). Notably, a functional link between Na/K-ATPase and K ATP has also been described (27).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated a role for Na/KATPase in the heart's response to ischemia reperfusion (39). Notably, a functional link between Na/K-ATPase and K ATP has also been described (27).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Inhibition of Na ϩ /K ϩ -ATPase reduced the infarct size-limiting effect by IPC, 14 suggesting the important role of the ATPase. Functional interaction between the sarcolemmal K ATP channel and Na ϩ /K ϩ -ATPase has been reported.…”
Section: Contribution Of Namentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the inhibition of Na ϩ /K ϩ -ATPase also abolished the infarct size-limiting effect induced by IPC. 14 Although these candidates are considered to modify intracellular Na ϩ kinetics that is critically coupled with the subsequent Ca 2ϩ overload, the details of the change in Na ϩ kinetics are not clear.…”
mentioning
confidence: 99%
“…IPC limits the inhibition of sarcolemmal Na + -K + ATPase activity in the acute phase of ischemia and increases Na + -Ca + exchange activity [22]. Haruna et al [23] recently reported that the infarct limiting effect of IPC may be modulated via an interaction between Na + -K + ATPase and sarcK ATP channels.…”
Section: Sarck Atp As a Distal Effectormentioning
confidence: 99%